2017
DOI: 10.1080/10408444.2017.1318354
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoparticle exposures from nano-enabled toner-based printing equipment and human health: state of science and future research needs

Abstract: Toner formulations used by laser printers (LP) and photocopiers (PC), collectively called “toner-based printing equipment” (TPE), are nano-enabled products (NEP) because they contain several engineered nanomaterials (ENM) that improve toner performance. It has been shown that during consumer use (printing), these ENM are released in the air, together with other semi volatile organic nanoparticles, and newly formed gaseous co-pollutants such as volatile organic compounds (VOC). The aim of this review is to deta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 95 publications
2
51
0
Order By: Relevance
“…A number of studies have focused on the exposure characterization of emissions from laser printers (14). Early on, it was documented that an increase in particle number concentrations of up to 3.8×10 4 particles/cm 3 with a count median diameter varying from 40–76 nm in an office during printing, which suggests the majority of measured particles have sizes less than 100 nm (PM 0.1 ) (1517).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have focused on the exposure characterization of emissions from laser printers (14). Early on, it was documented that an increase in particle number concentrations of up to 3.8×10 4 particles/cm 3 with a count median diameter varying from 40–76 nm in an office during printing, which suggests the majority of measured particles have sizes less than 100 nm (PM 0.1 ) (1517).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the evaluation of potential toxicity of the PEPs, evidence continues to grow in the published domain as summarized in a review paper (14) and includes both in vitro and in vivo toxicological studies as well as human health studies. In our previous studies, it was found that human small airway epithelial cells, microvascular endothelial cells, macrophages, and lymphoblasts showed substantial changes in cell viability, production of reactive oxygen species, release of inflammatory cytokines and modifications to the DNA methylation machinery (1820).…”
Section: Introductionmentioning
confidence: 99%
“…This notion, however, seems to be based on an incorrect interpretation of the work of Wensing et al30 Theegarten and colleagues were made aware that the cited work of Wensing et al30 does not contain any references or conclusions whatsoever to carbon nanoparticles in laser printer emissions 71. The aforementioned study by Pirela et al21 offers a comprehensive overview. A total of 54 studies were evaluated, of which 32 concerned emissions and 22 addressed toxicological effects from categories (b) and (c).…”
mentioning
confidence: 99%
“…The rate at which production of new ENPs and incorporation into NEPs occurred has far exceeded our ability to test all ENPs and LCPM released over the NEP life cycle using in vivo animal studies. This study will focus on a specific real-world LCPM: laser printer-emitted particles (PEPs) generated from nano-enabled toners which has been studied extensively by the authors and others over the last decade [18,19]. In US alone, 23 million printers are produced annually, and over 160,000 workers are employed in copier centers [20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%